2014
DOI: 10.1111/micc.12104
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Activate the miRNA/RhoA/ROCK2 Pathway in Endothelial Cells

Abstract: miR-200b and miR-200c are suppressed in AGE-induced endothelial cell injury, resulting in unregulated RhoA/ROCK2 signaling. Further studies are necessary to evaluate the therapeutic value of targeting miRNAs or their target genes for treatment of vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 43 publications
4
19
0
Order By: Relevance
“…Based on these findings, it is not surprising that overexpression of Smad7 significantly mitigated renal fibrosis in a rat unilateral ureteral obstruction model [32]. Conversely, Smad7-deficient diabetic mice exhibited more severe renal fibrosis, albuminuria, and inflammation compared with those with a normal genotype [27]. e results of these studies were consistent with our observation of downregulated Smad7 expression in rat kidney tissues exposed to a hyperglycemic environment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Based on these findings, it is not surprising that overexpression of Smad7 significantly mitigated renal fibrosis in a rat unilateral ureteral obstruction model [32]. Conversely, Smad7-deficient diabetic mice exhibited more severe renal fibrosis, albuminuria, and inflammation compared with those with a normal genotype [27]. e results of these studies were consistent with our observation of downregulated Smad7 expression in rat kidney tissues exposed to a hyperglycemic environment.…”
Section: Discussionsupporting
confidence: 86%
“…A series of recent studies have considerably furthered our understanding of the pathogenic role of Smad7 in DN [27][28][29]. e transforming growth factor-β (TGF-β)-Smad signaling pathway has been shown to be a key regulator of Evidence-Based Complementary and Alternative Medicine ECM homeostasis, a process closely associated with the development of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Rho associated proteins are involved in an abundant of cell processes, containing proliferation, cytoskeletal actin remodeling, differentiation, and the generation of ROS [21]. ROCK2 is one of isoforms of ROCK and the down-stream effector of RhoA which enhances cell motility via inhibition of myosin phosphatase [20,22].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…These results suggested that the histone methylation activity may have vital roles in SMYD3-mediated transactivation of miR-200c-3p. (60,61). As the results of the present study demonstrated the overexpression of SMYD3 directly transactivates miR-200c-3p, whether SMYD3 and miR-200c-3p supports or opposes each others' effects on the transcription of MYL9 and CYR61, two MRTF-A-dependent migration-related genes, was investigated.…”
Section: Histone Methylation Activity Is Essential In the Smyd3-mediamentioning
confidence: 73%